TOURISM DEVELOPMENT IN THE WORLD CULTURAL HERITAGE AREA OF SUBAK JATILUWIH, TABANAN, BALI - Susila, I Gede (E-Journal of Cultural Studies, 2018)
Subak Jatiluwih in Tabanan Regency, Bali, has double status. On the one hand the Subak (water irrigation system) is a tourist attraction (destination), and on the other hand its status is as World Cultural Heritage (Warisan Budaya Dunia or WBD). Related to that matter, this paper describes two things: (1) the development of tourism facilities in Subak Jatiluwih area, and (2) the financial input in managing Jatiluwih tourist attraction and its distribution. This is a qualitative study. The data found is analyzed using qualitative data analysis. The result of study shows that, regarding the double status as stated above, it is precisely within the perceptions of local community about the status of Subak Jatiluwih as WBD are related to "tourism brand". Therefore, the development of tourism facilities that violate the provisions of the law in the area of ??Subat Jatiluwih WBD was inevitable. On the rice fields in the subak, area parking lots of buses and restaurants have been built. Thus, there are some conversion of rice field into parking lots and restaurants in the area of ??the WBD. Specifically in relation to financial input in the management of DTW Jatiluwih, it turns out financial input reaches hundreds of millions of dollars even nearly 1 billion per month. The distribution of the results of the DTW (daerah tujuan wisata or tourist destination) management is conducted with the management of the parties based on justice that is tailored to the contribution and needs of each manager. This means that the greater the contribution and the needs of the parties involved in managing the DTW, the greater the share of the financial results it receives.